2012
DOI: 10.1039/c2dt31115a
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble, luminescent iridium(iii)–ytterbium(iii) complexes using dipyrido[3,2-a:2′,3′-c]phenazine derivatives as bridging units

Abstract: Amino-substituted dipyrido[3,2-a:2',3'-c]phenazine (L(1)) and dimethyl-dipyrido[3,2-a:2',3'-c]phenazine (L(2)) have been investigated as: (i) chromophores in cyclen-based ligands for lanthanide(III) ions; (II) ancillary co-ligands in cyclometalated iridium(III) complexes; (III) bridging, linker units in covalently linked, water-soluble bimetallic lanthanide(III) iridium(III) hybrid complexes. The dipyrido[3,2-a:2',3'-c]phenazine (dppz) derivatives can act as sensitising chromophores (λ(ex) 400 nm) for Yb(III),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…The emission maxima for complexes 3a-g show very little variation (627-630 nm), are broad and featureless, and typically characteristic of MLCT-based transitions. 24 This variation is less than that predicted by TD-DFT (see ESI †), possibly suggesting a diminished diimine contribution to the excited state. Corresponding excitation spectra showed that the complexes could be excited up to a wavelength of ca.…”
Section: Papermentioning
confidence: 81%
See 1 more Smart Citation
“…The emission maxima for complexes 3a-g show very little variation (627-630 nm), are broad and featureless, and typically characteristic of MLCT-based transitions. 24 This variation is less than that predicted by TD-DFT (see ESI †), possibly suggesting a diminished diimine contribution to the excited state. Corresponding excitation spectra showed that the complexes could be excited up to a wavelength of ca.…”
Section: Papermentioning
confidence: 81%
“…The product was used in subsequent reaction without further purification. 24 [Ir(epqc) 2 (bpy)]PF 6 3a.…”
Section: Synthesismentioning
confidence: 99%
“…Various types of lanthanide(III) complexes attached with Ir(III) complexes have also been reported (Fig. 8f) [82][83][84][85] . Generally, Ir(III) complexes show blue, green, and red luminescence at room temperature based on the MLCT transition bands.…”
Section: Light and Transition Metal Complexesmentioning
confidence: 91%
“…By choosing ligands judiciously, it is possible to tune the T1 energy of the iridium complex in such that it is sufficiently above the lanthanide D0, allowing for a photo-induced energy transfer. [9][10][11][12][13][14][15] Such systems have been employed in bioimaging, in particular for in vivo 1 O2 sensing. 16,17 Depending on the nature of the tether between the iridium complexes and other molecules, energy transfers can occur via two different mechanisms: i) Förster energy transfers, which are common in unconjugated tethers but decay exponentially with distance of electron-donating groups which raise the energy of the pic orbitals, thereby reducing their involvement in the frontier orbitals of the complex and properties of the excited state.…”
Section: Introductionmentioning
confidence: 99%